Composite Materials Containing Perfluorinated and Siloxane Units for Vertical Alignment of Liquid Crystals - Hegde, Gurumurthy; Alla, Rasha Ata; Komito, Lachezar; Morelli, Andrea; Chiellini, Emo; Galli, Giancarlo (Scientific Research Publishing Inc., 2013)
Here we report on the study of vertical alignment of a nematic liquid crystal due to the segregation between perfluorinated and the polysiloxane groups of a multi-component composite alignment material. The measured surface anchoring energy was found to depend on the relative amount of polysiloxane matrix in the composite material. These kind of self-assembly will reduce the preparation time for display by eliminating few steps.